Hubungan Status Ekonomi di Masa Pandemi, Status Gizi, Kunjungan ANC dengan Kejadian Anemia pada Ibu Hamil di PMB Maria Ulfa - Hanafi, Mala; Lami, Sumardiana; Putri, Syaifana (Lembaga Publikasi Ilmiah Nusantara, 2024)
Anemia is a global public health issue that can increase morbidity and mortality rates. Despite ongoing efforts, the prevalence of anemia remains high. This descriptive study employed a cross-sectional method aimed at gathering information regarding factors influencing the incidence of anemia among pregnant women, using medical records as the primary data source. The study was conducted from November 2021 to January 2022, involving 20 pregnant women as respondents. The data collected included independent variables (ANC visits, economic status, and nutritional status) and a dependent variable (the incidence of anemia), measured using a questionnaire. Based on the data table, among the 20 respondents with low economic status, 7 pregnant women (19.7%) did not suffer from anemia, whereas among the 20 respondents with high economic status, 6 pregnant women (19.0%) were found to have anemia. Statistical testing yielded a P-value of 0.014, indicating a significant relationship between economic status and the incidence of anemia. Analysis results showed an Odds Ratio (OR) of 2.500, suggesting that pregnant women with low economic status have a 2.5 times higher risk of developing anemia compared to those with higher economic status. It is recommended that midwives enhance their provision of counseling for pregnant women, particularly from the first trimester, regarding the dangers of anemia during pregnancy, and the effects of hemoglobin levels on both maternal health and fetal development.